ANALISIS SISTEM PENGAMAN BACKUP UNTUK MENGAMANKAN BUSBAR 150 Kv TERHADAP GANGGUAN DI GIS PECATU - I Nyoman Wardana; I Gede Dyana Arjana; Cok. Gede Indra Partha (Program Studi Teknik Elektro UNUD, 2021)
High power needs in badung area, especially Pecatu and Nusa Dua resulted in theneed for GIS development to increase power supply. GIS Pecatu uses a double busbar withOCR as its Backup safety, if one of the busbars is disrupted and there is no protection rele thatsecures the busbar, it will result in continuous power flow is disrupted.In this study, an analysis of the rele busbar setting and the appropriate protectionsetting as a reference protection system in GIS Pecatu. The results of the calculation of currentsetting obtained the working current value (Iset) OCR of 1339 A and (Iset) GFR 223 A anddelay time 0.53 seconds, actual working time rele 0.35 Standard Inverse, and the value of shortcircuit interference current calculation from PLN 11.58 kA and based on simulation resultsobtained 11.46 kA with a percentage of errors of 0.12%.